Aprendendo com desastres naturais : inundações e resiliência em Vila Velha, ES - Pereira, Winnie Bruna de Souza (2017)
The occurrence of disasters through natural or human actions can be frequent and usually contributes to the deterioration of the environment and local memory. The incidence of these disasters has become increasingly common in cities, particularly in areas